Analisis strategi penyelesaian kredit bermasalah di KC PD BPR Artha Galunggung Cabang Manonjaya - Al Rasyid, Dwiyan (Nur Science Institute, 2025)
This study aims to analyze the quality of credit distribution, strategies for resolving non-performing loans (NPLs), and identify the obstacles and factors that contribute to loan defaults at KC. PD. BPR Artha Galunggung, Manonjaya Branch. A mixed-methods approach was employed, combining quantitative analysis of credit collectibility data with qualitative insights from interviews and observations. The findings reveal that although credit distribution has increased, its quality remains relatively unhealthy, as indicated by a rising NPL ratio over the past three years, particularly in 2023. The bank has implemented several handling strategies, including direct visits to borrowers, business condition analyses, credit restructuring, and rescheduling of repayments. However, these measures have not been fully effective in reducing the level of non-performing loans. The root causes of problem loans stem from both internal factors, such as weak creditworthiness analysis, and external factors, including declining business performance and borrowers’ financial incapacity. Additional challenges include difficulties in communication with debtors and the limited effectiveness of the approaches taken. Therefore, strengthening credit analysis systems and adopting more human-centered and adaptive resolution strategies tailored to borrowers’ economic conditions are essential to lowering NPLs and maintaining banking health.